A Learner-centred Input–Output Model - Mohapatra, J. K.; Mahapatra, Madhuri; Parida, B.K. (JOURNAL OF INDIAN EDUCATION, 2012)
Meaningful learning can be maximised by knowing what are the contributing structures (inputs) the learners carries with him/her into the classroom and using which he/she is going to construct new structures (output). In this research paper, a four-dimensional input has been presented and key information for the measurement of the inputs in the classroom situation has been discussed. The output has been delineated in the conceptual change model of the constructivist approach.